The Impact of Indonesia’s Village Fund (Dana Desa) on Village Head Election - Anshari, Khairullah; Khaidir, Said; Marthalina (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
Through the implementation of the Village Law in 2014, the Indonesian government seeks to promote rural development and village autonomy by decentralizing power. The 2014 Village Law has two important points: the village fund and the extension of a village head’s term. This article tested to what extent the village fund has impacted the village head election and whether the village fund has improved villagers’ political participation in running for the village head election. The method used in this study is quantitative through a survey of 96 random village head candidates in the 2016 village head election in 117 villages in Banjar Regency, South Kalimantan. The findings show that the village funds have an impact on the quality of the nomination of village heads and facilitate the public’s involvement in the election. This phenomenon underscores the importance of village funds in encouraging democratic practices and the grassroots community’s participation in village governance. Changes in regulations of village fund implementation influence the participation of village residents in running for village head election, encouraging them to participate in the democratic process at the village level.